Nghiên cứu chế tạo điện cực compozit oxit spinel NixCo3-xO4/polypyrol xúc tác phản ứng khử oxy - Lê Hiền, Nguyễn Thị; Kiều Duyên, Phạm Thị (Vietnam Journal of Chemistry, 2014)
In this work we have studied the polypyrrol/oxide (Ppy/oxit) composite films electrodeposited on glassy carbon for electrocatalyst application of oxygen reduction reaction. Three oxides used NiO, Co3O4 and Ni0.3Mn2.7O4 with very small size was prepared by thermal decomposition of nitrate salts. These oxides were incorporated in the polypyrrole films during the electrodeposition respectively to form Ppy/oxide composite films. Among the composite films obtained the polypyrrole/Ni0.3Mn2.7O4 gives the best electrocatalytic effect.